Hubungan Academic Burnout dengan Academic Procrastination pada Mahasiswa - Yunalia, Endang Mei; Suharto, Idola Perdana Sulistyoning; Samudera, Wahyu Sukma; Radiah, Siti (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2023)
The high burden of students during lectures will usually be followed by a feeling of boredom and a lack of enthusiasm in learning or in completing assignments. This feeling felt by students is called academic burnout. Academic burnout that is felt by students can eventually lead to delays in completing assignments inlectures which is called academic procrastination. The purpose of this study is to examine the correlation between academic burnout and academic procrastination in college students. This research is a correlational analytic study with a cross sectional approach. The population in this study were students at one of the universities with a total research sample of 139 respondents who were selected using total sampling techniques. The results showed that almost half of the respondents with moderate academic burnout level had moderate academic procrastination, namely as many as 52 respondents (37,4%). Based on the results of statistical tests using the Spearman Rank test, the p value was 0,012, which means there is a relationship between academic burnout and academic procrastination in students. The strength of the relationship between academic burnout and academic procrastination in students is very weak, as evidenced by the correlation coefficient value of 0,212 with a positive relationship direction, namely the higher the level of academic burnout, the level of academic procrastination will also increase. Students should develop time management skills to complete course assignments. This is necessary to prevent academic burnout and academic procrastination.